(3GdfXGe GdbGfhfj dCehGd GdOhdI GdNGUI (B=s Legal regulation to the special properties of the country - (3YHO GdMejO, CMeO WdGds ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3Ef eYXe GdeDdaGJ GdabgjI GdJj JfGhdJ ehVhY GdCehGd GdeedhcI ddOhdI HUaJgG TNUG eYfhjG YGeG, JQcR Ydi CehGd GdOhdI GdYGeI, aJYfi HJYQja gPg GdCehGd hHjGf WHjYJgG heYGjjQ JejjRgG YeG ShGgG ef GdCehGd, hGdCZQGV GdeNUUI Ch GdeQUhOI dgG, hhSGFd GdMeGjI GdhGQOI aj GdOSJhQ hhSGFd GdMeGjI GdeOfjI hGdLfGFjI dgPg GdCehGd(B. (3hfGOQG eG JHMK gPg GdeDdaGJ aj ehVhY GdfXGe GdbGfhfj dCehGd GdOhdI GdNGUI, MjK JcJaj eYXe gPg GdeDdaGJ HEjQGO ETGQI HSjWI YfgG, hGdSHH aj Pdc jQLY Edi Cf eYXe GdeDdaGJ GdabgjI GdJj JJfGhd ehVhY GdCehGd GdYGeI, gj eDdaGJ JONd aj fWGb GdbGfhf GdEOGQj, ajJLfH abgGA GdbGfhf GdYGe GdNhV aj ehVhY GdfXGe GdbGfhfj dCehGd GdOhdI GdNGUI chfgG ef GdehGVjY GdJj JONd aj fWGb GdbGfhf GdNGU ef LgI, hef LgI CNQi aEf eDdaGJ GdbGfhf GdYGe ZjQ eYfjI HTcd eHGTQ HHMK ehGVjY JONd aj fWGb GdbGfhf GdNGU, cPdc fdGMX Cf eYXe GdJbfjfGJ GdeOfjI bO NdJ ef JYQja jJfGhd GdCehGd GdNGUI ddOhdI, hGbJUQJ Ydi EjQGO JYQja ddCehGd GdYGeI hhSGFd GdMeGjI GdebQQI dgG, dPG hLOfG ef GdVQhQj Cf fJfGhd aj HMKfG gPG GdfXGe GdbGfhfj dCehGd GdOhdI GdNGUI(B.s
(3JUeje hEfJGL (B: (3ecJH OGQ GdKbGaI ddJUeje hGdEfJGL(B.s
(3GdCUd CWQhMI eGLSJjQ(B-(3eLdS GdCcGOjejI GdYdjG ddOQGSGJ GdYdejI hGdEfSGfjI(B.s
(3HHdjhLQGajI (B: (3UaMI (B225-240.s
Keywords: (3GdeGdjI GdYGeIs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3GdVQGFHs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs